The effects of physical activity interventions on preventing weight gain and the effects on body composition in young adults with intellectual disabilities: systematic review and meta‐analysis of randomized controlled trials. Issue 4 (30th June 2015) - Harris, L.; Hankey, C.; Murray, H.; Melville, C.
Summary: The aim of this study was to examine the literature on randomized controlled trials examining the efficacy of physical activity interventions to prevent weight gain and the effects on body composition in young adults with intellectual disabilities.A systematic search of Medline, Emabse, CINHAL, PsychINFO, Cochrane library and ERIC was conducted from 1946 to September 2014. Eligibility criteria included; randomized controlled trials of a physical activity intervention: objective measure of body weight and body composition; young adults (age range 16–24 years) with intellectual disabilities. Six studies met the eligibility criteria. The interventions varied in their prescription of physical activity including aerobic and strength‐based activities. The mean duration of the interventions was 15.3 (range 10–21 weeks). There was no significant effect of physical activity interventions on body weight (weighted mean difference: −0.17 kg, 95% confidence interval, −1.04 kg to 0.72 kg) and body composition outcomes. The meta‐analysis showed that physical activity interventions did not prevent weight gain in young adults with intellectual disabilities. Published studies are inadequate to form firm conclusions. Future longer term studies of interventions specifically designed for this population group are required to elucidate the effects of physical activity interventions on body composition and the prevention of weight gain in young adults with intellectual disabilities.